EXPLORING THE LOCAL FOOD CONSUMPTION AND KNOWLEDGE RETENTION FOR STUNTING PREVENTION - Pratiwi, Dessy; Muaris, Hindah; Musiawan, Ria; Basrowi, Ray Wagiu; Kinesya, Edwin (Ridwan Institute, 2025)
Background: Stunting in children may increase their risk of infection, problem associated with growth and development, and also intelligence. Higher than national stunting rate, Central Kalimantan have 26.9% stunting in 2022. Stunting prevention programs such as utilization of local food are encouraged. Objectives: This study explores behaviour and the impact of education to the knowledge of Central Kalimantan’s resident of local food consumption to decrease stunting in children. Methods: A secondary data from cross-sectional survey conducted by Indonesian Gastronomy Community in two regencies within Central KalimantanProvince was analyzed. Participants voluntarily fulfill immediate survey after education (post-1), and 3-month after education (post-2) survey. Compiled data are further analyzed to explore participants understanding. Results: A total of 152 post-1 survey and 122 post-2 survey are compiled. Participants answers dietary habit consists of fish (97.54%), vegetable (95.90%), fruits (50%), meat (31.97%), tempeh/tofu (28.68%), egg (27.87%), chicken (8.19%), and milk (8.19%), in descending order. Most consumed plant-based protein are tempeh (76.22%) and tofu (72.13%). Decreased score was observed from the immediate test to the three months after education and survey. Conclusion: Residents of Central Kalimantan Province in Indonesia primarily rely on fish, tempeh, and tofu as their main protein sources. These foods are high in protein and readily available in their local environment. To aid in stunting prevention, regular educational programs should be implemented to ensure long-term retention of knowledge